Հայերենի և անգլերենի հուզագնահատողական արտահայտությունների իմաստակառուցվածքային շերտերը. ՀԳԱ-ների դիրքն ու ամբողջականությունը - Գրիգորյան, Գոհար; Ղահրամանյան, Սվետլանա (Զանգակ հրատ.)
Психолингвистический, познавательный характер ЭОВ обусловлен познавательными навыками и эмоциональным состоянием духовного мира человека. Эмоции формируют языковую деятельность, выполняют такие познавательные функции, как оценка предметов и событий, стимуляция к действию, регулируют поведение людей. В армянском и английском языках ЭОВ также имеют структурно-смысловые различия, обусловленные данными культурами. Их всестороннему изучению способствует межъязыковой сопоставительный полисимтоматический анализ. The psycholinguistic, cognitive character of emotional-attitudinal expressions is conditioned by cognitive skills and emotional state of the spiritual world of a human being. Emotions formulate language activities, such as cognitive functions, such as how to evaluate things and events, stimulate to actions and regulate peoples՛ behavior. In both Armenian and English languages, the emotional –attitudinal expressions have structural-semantic differences conditioned by the cultures. The polysymtomatic comparative interlingual analysis greatly contributes to the thorough study of emotional – attitudinal expressions.
Keywords: Ուսուցման և դասավանդման մեթոդիկա